2018
DOI: 10.1101/372797
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Engineered cell-to-cell signalling within growing bacterial cellulose pellicles

Abstract: Bacterial cellulose is a strong and flexible biomaterial produced at high yields by Acetobacter species and has applications in healthcare, biotechnology and electronics. Naturally, bacterial cellulose grows as a large unstructured polymer network around the bacteria that produce it, and tools to enable these bacteria to respond to different locations are required to grow more complex structured materials. Here, we introduce engineered cell-to-cell communication into a bacterial cellulose-producing strain of K… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…In recent years, primary advancements in applied ELM technologies have centered on nonmedical applications for design problems in other industries (e.g., electronics, construction, devices, and computing). Engineers have produced electrically conductive biofilms and advanced electrical biosensors using Curli fibers [45][46][47][48] and bacterial cellulose pellicles [49]. Examples of enabling technologies and proofs of concept also exist in the literature related to engineering living photovoltaics [50], electronics [51], and photonic materials [19].…”
Section: From Single Organisms To Consortiamentioning
confidence: 99%
“…In recent years, primary advancements in applied ELM technologies have centered on nonmedical applications for design problems in other industries (e.g., electronics, construction, devices, and computing). Engineers have produced electrically conductive biofilms and advanced electrical biosensors using Curli fibers [45][46][47][48] and bacterial cellulose pellicles [49]. Examples of enabling technologies and proofs of concept also exist in the literature related to engineering living photovoltaics [50], electronics [51], and photonic materials [19].…”
Section: From Single Organisms To Consortiamentioning
confidence: 99%
“…Recent work in the area of synthetic biology and the cellulose producing bacterium Komagataeibacter rhaeticus may lead to the production of patterned biological materials with unique properties in terms of macrostructure and function. Walker et al [66]. have engineered K. rhaeticus with genetic manipulation tools to insert synthetic circuits into the cellulose pathway which respond to intercellular signalling.…”
Section: Nanocellulosementioning
confidence: 99%
“…These studies together give a comprehensive guide for the construction of vectors of a high potential to be effective in the numerous species from this genus. These recent achievements include the use of quorum sensing (QS) synthetic biology elements known to be functional in E. coli (Florea et al 2016 ; Walker et al 2018 ). The first example of employment of these elements was the application of inducible lux promoter and luxR gene for modification of K. rhaeticus strain (Florea et al 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…This study showed that the capability of cellulose production was lowered and eventually switched off with increasing concentration of N -acyl homoserine lactone (AHL) in the media. Another study reported the construction of Sender and Receiver recombinant K. rhaeticus strains (Walker et al 2018 ). The first strain produced AHL in response to an environmental signal, while the second strain induced recombinant protein expression (red fluorescent protein, RFP) in response to AHL in a concentration-dependent manner.…”
Section: Introductionmentioning
confidence: 99%